STUDY OF THE EFFECT OF IMMOBILIZATION STRESS ON ERYTHROCYTE MEMBRANES (Experimental biology, 2023)
This article discusses the effect of acute and chronic immobilization stress on erythrocyte membranes. The intensive development of science and technology has brought into human life, along with positive phenomena, a number of unfavorable factors: hypodynamia, excessive nervous, physical exertion, professional and household stresses. Among them, hypodynamia is a lifestyle characterized by a decrease in motor activity, which negatively affects human health. This is a common situation nowadays. Hypodynamia leads to metabolic and energy disorders in the body, cardiovascular diseases, diseases of the gastrointestinal tract, overweight, early aging, a decrease in the body's ability to resist various diseases, changes in the general condition of the body, etc. Such a stressful effect is observed at the cellular and molecular level. As stress increases, metabolic disorders appear, activation of free radical oxidation leads to disruption of the main: barrier, receptor, catalytic functions of biological membranes. As a result, it leads the human body to various pathological conditions. Currently, more attention is being paid to an integrated approach to the treatment and prevention of diseases. This article discusses the effect of acute and chronic immobilization stress on erythrocyte membranes. As a result of the research, it was found that the effect of immobilization stress leads to a decrease in the osmotic and peroxide resistance of erythrocytes and an increase in the hemoglobin yield. The use of vitamin E reduces the damaging effect of both acute and chronic immobilization stress. Consequently, antioxidants can protect the body from the damaging effects of stress factors.
Keywords: erythrocyte membrane, acute and chronic immobilization stress, hemolysis, vitamin E.